Large-scale, probabilistic salinity mapping using airborne electromagnetics for groundwater management in Zeeland, the Netherlands. (27th July 2018) - Delsman, Joost R; van Baaren, Esther S; Siemon, Bernhard; Dabekaussen, Willem; Karaoulis, Marios C; Pauw, Pieter S; Vermaas, Tommer; Bootsma, Huite; de Louw, Perry G B; Gunnink, Jan L; Dubelaar, C Wim; Menkovic, Armin; et al.
Abstract: Seawater intrusion has often resulted in scarce fresh groundwater resources in coastal lowlands. Careful management is essential to avoid the overexploitation of these vulnerable fresh groundwater resources, requiring detailed information on their spatial occurrence. Airborne electromagnetics (EM) has proved a valuable tool for efficient mapping of ground conductivity, as a proxy for fresh groundwater resources. Stakeholders are, however, interested in groundwater salinity, necessitating a translation of ground conductivity to groundwater salinity. This paper presents a methodology to construct a high-resolution (50 × 50 × 0.5 m 3 ) 3D voxel model of groundwater chloride concentration probability, based on a large-scale (1800 km 2, 9640 flight line kilometres) airborne EM survey in the province of Zeeland, the Netherlands. Groundwater chloride concentration was obtained by combining pedotransfer functions with detailed lithological information. The methodology includes a Monte Carlo based forward uncertainty propagation approach to quantify the inherent uncertainty in the different steps. Validation showed good correspondence both with available groundwater chloride analyses, and with ground-based hydrogeophysical measurements. Our results show the limited occurrence of fresh groundwater in Zeeland, as 75% of the area lacks fresh groundwater within 15 m below ground surface. Fresh groundwater is mainly limited to the dune area and sandy creek ridges. In addition, significant fresh groundwater resources were shown to exist below saline groundwater, where infiltration of seawater during marine transgressions was hindered by the presence of clayey aquitards. The considerable uncertainty in our results highlights the importance of applying uncertainty analysis in airborne EM surveys. Uncertainty in our results mainly originated from the inversion and the 3D interpolation, and was largest at transition zones between fresh and saline groundwater. Reporting groundwater salinity instead of ground conductivity facilitated the rapid uptake of our results by relevant stakeholders, thereby supporting the necessary management of fresh groundwater resources in the region.